Modelling the effects of sea-level rise and sediment budget in coastal retreat at Hermenegildo Beach, Southern Brazil (Brazilian Journal of Oceanography, 2018)
Climate change effects such as accelerated sea-level rise, wave climate alteration and disturbances on sediment-budgets are anticipated to lead to a range of adverse impacts in coastal regions around the world. A rise in sea-level is expected to cause shoreline recession, and a sediment deficit can have a similar effect. Since large uncertainties exist in relation to sea-level rise rates and sediment budgets, it is relevant to determine how sensitive the coast is to each of these disturbances. In this context, this paper provides a quantitative evaluation of each of these parameters in terms of modeled coastal recession through risk-based assessments using an aggregated coastal model, the DRanSTM (Dilating Random Shoreface Translation Model). In each separate computer simulation, a sediment budget and a sea-level scenario were set for an erosional coastal stretch: Hermenegildo Beach, Rio Grande do Sul state in southern Brazil. Effects of changes in wave climate were not directly considered in this study. However, indirect measures of such changes should be reflected on coastal sediment budgets. Simulation results demonstrate that under present-day sea-level rise rates, sediment deficit exerts control over coastal recession. Conversely, under the higher forecasted sea-level rise for the year 2100, mean shoreline recession will be dictated by sea-level rise, considering historical sediment deficit will be sustained.